BOHDAN LEPKIY IS A SHEVCHENKO EXPERT - Братусь, І. В. (Proceedings of National Aviation University (archive), 2021)
The works of Bohdan Lepky and the main trends in the development of the historical and biographical genre, the problems of which require comprehensive consideration and understanding, are considered. The place of Ukrainian biographical literature in the world literary process seems to be important.